Assessment of genetic variability in blackgram (Vigna mungo) under rainfed conditions of Jammu and Kashmir - KUMAWAT, RADHESHYAM; KUMAR, SANJEEV; KASHYAP, SUBHASH C; SINGH, ADITI (The Indian Journal of Agricultural Sciences, 2024)
Analysis of variance for 11 traits under investigation revealed significant variability among the genotypes. This indicated an extensive range of genetic variability existed among the genotypes of blackgram. On the basis of higher mean performance than general mean, genotype PU-19 reported higher seed yield/plant along with higher number of seeds/pod, number of clusters/plant, number of pods/ cluster. Hence, recommended for the enhancement of area under this variety particular in rainfed ecology. On pooled basis seed yield/plant had significant correlation with all yield contributors except plant height. Number of seeds/pod, number of clusters/plant, number of pods/cluster and seed yield/plant signified high heritability as well as high genetic advance as percentage of mean indicated the presence of additive gene action, while plant height and number of pods/ plant exhibited modest heritability as well as modest genetic advance as percentage of mean. Consequently, suggesting the presence of additive gene action and phenotypic selection for such traits may be useful in the future of blackgram improvement programs.